Application of tumor pH/hypoxia-responsive nanoparticles for combined photodynamic therapy and hypoxia-activated chemotherapy - Zhang, Zhang; Feng, Jintang; Zhang, Tianzhu; Gao, An; Sun, Chunyang (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer selectivity, including targeted internalization and accelerated drug release in tumor cells, remains a major challenge for designing novel stimuli-responsive nanocarriers to promote therapeutic efficacy. The hypoxic microenvironment created by photodynamic therapy (PDT) is believed to play a critical role in chemoresistance. We report dual-responsive carriers (DANPCT) that encapsulate the photosensitizer chlorin e6 (Ce6) and hypoxia-activated prodrug tirapazamine (TPZ) to enable efficient PDT and PDT-boosted hypoxia-activated chemotherapy. Due to TAT masking, DANPCT prolonged payload circulation in the bloodstream, and selective tumor cell uptake occurred via acidity-triggered TAT presentation. PDT was performed with a spatially controlled 660-nm laser to enable precise cell killing and exacerbate hypoxia. Hypoxia-responsive conversion of the hydrophobic NI moiety led to the disassembly of DANPCT, facilitating TPZ release. TPZ was reduced to cytotoxic radicals under hypoxic conditions, contributing to the chemotherapeutic cascade. This work offers a sophisticated strategy for programmed chemo-PDT.